منظمة تعاون شنغهاي كتحالف مناهض للولايات المتحدة الأمريكية (Latakia University Journal - Economic and Legal Sciences Series, 2013)
بالاستناد إلى نظرية توازن القوى، فإن القوى الدولية تميل إلى تشكيل التكتلات والاتحاد مع بعضها لمواجهة الهيمنة، ومن الطبيعي بعد ظهور الولايات المتحدة الأمريكية كقوة وحيدة مهيمنة على الشؤون الدولية أن تولد ردود فعل معاكسة من جانب القوى الدولية الأخرى لمواجهة هذه الهيمنة ومحاولة تطويقها. لقد كانت روسيا والصين من أبرز القوى الدولية التي عملت على خلق مناخ دولي من أجل مواجهة محاولات ملء الفراغ الذي نجم عن تفكك الاتحاد السوفيتي من جانب الولايات المتحدة الأمريكية وبشكل خاص في جمهوريات آسيا الوسطى، ولذلك عملت على إنشاء تكتل إقليمي أطلقت عليه "منظمة تعاون شنغهاي". هذه الدراسة سوف تدرس إمكانية أن تكون منظمة تعاون شنغهاي كتحالف قادر على الوقوف في وجه التمدد الأمريكي في جمهوريات آسيا الوسطى، وفيما إذا كانت هذه المنظمة قادرة أن تكون كقطب مواز لهيمنة الولايات المتحدة الأمريكية. إنّ النتائج النهائية لهذا البحث ستُظهر أنّ منظمة تعاون شنغهاي تحالف موجه من أجل منع التأثير الاقتصادي والسياسي للولايات المتحدة الأمريكية في جمهوريات الاتحاد السوفيتي السابق في آسيا الوسطى.  According to the balance of power concept, nations tend to unite for opposing hegemony. Therefore, for the leading position of the US and its ability to project power globally, there should be an opposite and equal reaction from the other emerging power centers. Since the collapse of the USSR, the hegemonic position of the United States has been unchallenged. However, there is a possibility that it might be counterbalanced in future by the growing political influence of emerging powers, like Russia and China, which have already succeeded in countering the US influence in some parts of Eurasia through the mechanism known as the Shanghai Cooperation Organization (SCO). This study analyzes whether the SCO is an alliance directed against the United States and whether it has a potential to become a counterweight to the hegemony of the US. The results of this thesis research will show that the SCO is a regional alliance intended to restrain the political and economic influence of the United States in the post-soviet space.